States in history - Hall, John A., 1949- (Oxford [Oxfordshire] UK ; New York, NY, USA : B. Blackwell, 1986)
The state has been the subject of lively debate in modern social science, but the abstract and theoretical nature of much of the work is inaccessible. This volume remedies the situation by testing the adequacy of recent theories of the state against the historical record. The collection produces sustained answers to such key questions as the nature of state autonomy, the state's effect on economic development, and the role of nomads in their resistance of the state. While offering a fresh approach, the book maintains a firm empirical grounding in specific societies, from hunter-gatherers to present-day South America. Among the states discussed are Sumer, Imperial China, the states of classical Islam, city-states, the various capitalistic states and the Soviet state. Particular attention is paid to patterns of state formation and the erosion of the nation-state's autonomy by global political dynamics. The distinguished contributors are Clive Gamble, Patricia Crone, Ernest Gellner, Peter Burke, Michael Mann, Colin Crouch, Karen Dawisha, Anthony D. Smith, J.G. Merquior and Susan Strange.
Includes bibliographical references and index.
Keywords: Constitutional history; Comparative government; State, The